Silk biomaterials for tissue engineering and regenerative medicine - Kundu, S. C. (Amsterdam: Elsevier, Woodhead Publishing, 2014)
"Silk is increasingly being used as a biomaterial for tissue engineering applications, as well as sutures, due to its unique mechanical and chemical properties. Silk Biomaterials for Tissue Engineering and Regenerative Medicine discusses the properties of silk that make it useful for medical purposes and its applications in this area"--
Introduction to silk biomaterials / D. Naskar, R.R. Barua, A.K. Ghosh and S.C. Kundu -- Applications of silk biomaterials in tissue engineering and regenerative medicine / S. Das and U. Bora, and B.B. Borthakur -- Processing of Bombyx mori silk for biomedical applications / B.D. Lawrence -- Silk nanostructures based on natural and engineered self-assembly / N.E. Kurland, D.L. Presnall and V.K. Yadavalli -- Electrospun silk sericin nanofibers for biomedical applications / M.M.R. Kahn, and M. Tsukada -- Silk Fibroin microfiber and nanofiber scaffolds for tissue engineering and regeneration / G. Freddi and U. Armato -- Silk powder for regenerative medicine / R. Rajkhowa and X. Wang -- Biochemical and biophysical properties of native Bombyx mori silk for tissue engineering applications / A.R. Murphy and I.S. Romero -- Structure and properties of spider and silkworm silk for tissue scaffolds / G.V. Guinea, M. Elices, J. Pérez-Rigueiro and G.R. Plaza -- Types and properties of non-mulberry silk biomaterials for tissue engineering applications / S. Jasmine and B.B. Mandal -- Bio-response to silk sericin / P. Aramwit -- Biodegradation behavior of silk biomaterials / M. Li and J. Li -- Capillary growth behavior in porous silk films / L. Bai -- Silk biomaterials for intervertebral disk (IVD) tissue engineering / M. Bhattacharjee and S. Ghosh -- Silk scaffolds for dental tissue engineering / S.K. Jindal, M. Kiamehr and X.B. Yang -- Silk for cardiac tissue engineering / C. Patra and F.B. Engel -- Silk for dermal tissue engineering / A.T. Hodgkinson and A. Bayat -- Silk scaffolds for three-dimensional (3D) tumor modeling / S. Talukdar and S.C. Kundu -- Silk hydrogels for tissue engineering and dual-drug delivery / K. Numata -- Silk for pharmaceutical and cosmeceutical applications / J. Wong, H.-K. Chan and W. Chrzanowski.
Includes bibliographical references and index.
Keywords: Biomedical materials; Tissue engineering; Silk; Biocompatible Materials; Silk; Guided Tissue Regeneration; Tissue Engineering; Biomedical materials